2016
DOI: 10.1007/s11629-015-3604-9
|View full text |Cite
|
Sign up to set email alerts
|

Review of studies on land use and land cover change in Nepal

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(67 citation statements)
references
References 50 publications
13
54
0
Order By: Relevance
“…However, our study on Dudh Koshi did not showed the slight reduction in crop farming during 2010 described for the larger Koshi River Basin [12]. Nevertheless, since our study area focuses on the mountain environment, our outcomes seems to confirm the conclusion of another recent study (2016) that "agriculture practices and patterns that were once intensely distributed in lowland areas have spread to higher altitudes" [13].…”
Section: Resultssupporting
confidence: 77%
“…However, our study on Dudh Koshi did not showed the slight reduction in crop farming during 2010 described for the larger Koshi River Basin [12]. Nevertheless, since our study area focuses on the mountain environment, our outcomes seems to confirm the conclusion of another recent study (2016) that "agriculture practices and patterns that were once intensely distributed in lowland areas have spread to higher altitudes" [13].…”
Section: Resultssupporting
confidence: 77%
“…Previous studies of LULC in Nepal as a whole have included the KRB as a major part of their research [31,47] and patterns that were once intensely distributed in lowland areas have spread to higher altitudes [5]. The three datasets show that the rate of cropland change increased between 1978 and 1992, and then decreased slightly by 2010.…”
Section: Changing Trend Of Cropland Statusmentioning
confidence: 96%
“…By 1992 and 2010, a large area of cropland cover existed. This means that agriculture practices and patterns that were once intensely distributed in lowland areas have spread to higher altitudes [5]. The three datasets show that the rate of cropland change increased between 1978 and 1992, and then decreased slightly by 2010.…”
Section: Changing Trend Of Cropland Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Anthropogenic activities have been the dominant force shaping land use in recent years [3], although, their impacts vary spatially and temporally [4]. In recent decades, global land use change has been characterized by urban area growth and expanding agricultural land [5].…”
Section: Introductionmentioning
confidence: 99%